2021
DOI: 10.3389/fvets.2021.663175
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing of the Canine Cytochrome P450 CYP2C41 Gene and Genotyping of Its Polymorphic Occurrence in 36 Dog Breeds

Abstract: Cytochrome P450 (CYP) drug metabolizing enzymes play an important role in efficient drug metabolism and elimination. Many CYPs are polymorphic and, thereby, drug metabolism can vary between individuals. In the case of canine CYP2C41, gene polymorphism was identified. However, as the first available canine genome sequences all were CYP2C41 negative, this polymorphism could not be clarified at the genomic level. The present study provides an exact characterization of the CYP2C41 gene deletion polymorphism at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Among Canids, CYP2C41s show polymorphism as a complete loss in several breeds [ 53 ], suggesting some dogs have contracted CYP2Cs. This further suggests that other species might also show polymorphism or copy number variants within species, providing further justification for the importance of genomic analyses that use several individuals to conclude isoform numbers in each species.…”
Section: Discussionmentioning
confidence: 99%
“…Among Canids, CYP2C41s show polymorphism as a complete loss in several breeds [ 53 ], suggesting some dogs have contracted CYP2Cs. This further suggests that other species might also show polymorphism or copy number variants within species, providing further justification for the importance of genomic analyses that use several individuals to conclude isoform numbers in each species.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we also showed here that using publicly available bioinformatic resources like RNA-Seq databases can prevent such errors, and may support experimental data additionally. Breed-specific genetic variants in dogs have been reported before [34]. In this study, however, Boxer breed-specific differences cannot account for the "missing" sequence since another Boxer genome (Dog10K_Boxer_Tasha; Figure 9) and an RNA-Seq dataset from a Boxer (Figure 1D) both apparently contained the complete sequence.…”
Section: Discussionmentioning
confidence: 64%
“…We observed some genetic variability in OCT1 between individual dogs of different dog breeds that may have clinical relevance. Genetic variability in dog CYP enzymes, such as CYP1A2 and CYP2C41, or the efflux transporter MDR1/P-glycoprotein leading to a loss-of function phenotype are well-known for their effect on the efficacy and safety of drug treatment for dogs [34,[40][41][42]. The most well-known is the severe sensitivity to ivermectin and other antiparasitic drugs due to a 4-bp deletion in the canine MDR1 gene [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…However, not all polymorphisms result in enzymatic deficits, indicating that the capacity of the mutant CYP is not always reduced [ 39 ]. In the case of dogs, this implies that, based on the available data and inconsistencies between breeds, therapeutic dosing can be less efficacious in some dogs due to high enzymatic biotransformation, increased clearance, and minimal plasma concentrations [ 42 ], or could be attributed to a metabolically less active enzyme that produces fewer active metabolites [ 39 ].…”
Section: Clinical Pharmacology Of Tramadolmentioning
confidence: 99%
“…Conversely, cats are known to alter the metabolism of medications, given their enzymatic deficiency in functional UGT (UGT1A6 and UGT1A9), N-acetyltransferase and thiopurine S-methyltransferase. This loss reduces or completely suppresses the CYP catalytic activity, resulting in slow clearance, a higher plasma concentration of some compounds, and an enhanced risk of developing more adverse effects and toxicity [ 42 ]. To date, it remains unknown which feline CYP enzyme is responsible for the conversion of tramadol to M1 [ 43 ]; however, an in vitro report by Izes et al [ 44 ] revealed that the rate of depletion of M1 in dogs exhibited an intrinsic clearance (Cl int ) of 22.8 μl/min/mg, whereas in feline microsomes, the concentration of M1 was not depleted owing to the lack of CYP2B-like metabolism in this species.…”
Section: Clinical Pharmacology Of Tramadolmentioning
confidence: 99%